2002
DOI: 10.1103/physrevb.65.184405
|View full text |Cite
|
Sign up to set email alerts
|

Probability-changing cluster algorithm for two-dimensionalXYand clock models

Abstract: We extend the newly proposed probability-changing cluster (PCC) Monte Carlo algorithm to the study of systems with the vector order parameter. Wolff's idea of the embedded cluster formalism is used for assigning clusters. The Kosterlitz-Thouless (KT) transitions for the two-dimensional (2D) XY and q-state clock models are studied by using the PCC algorithm. Combined with the finite-size scaling analysis based on the KT form of the correlation length, ξ ∝ exp(c/ T /TKT − 1), we determine the KT transition tempe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
95
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 22 publications
19
95
2
Order By: Relevance
“…Monte Carlo simulations of the standard version with N = 6, 8, 12 were performed in Ref. [6]. Results for the critical index η agree well with the analytical predictions obtained from the Villain formulation of the model.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Monte Carlo simulations of the standard version with N = 6, 8, 12 were performed in Ref. [6]. Results for the critical index η agree well with the analytical predictions obtained from the Villain formulation of the model.…”
Section: Introductionsupporting
confidence: 66%
“…[7,8] and those for N = 6, 8 and 12 of Ref. [6], one can verify that β (1) c (N) approaches the 2D XY value, β (1) c = 1.1199, exponentially in N or even faster, while β (2) c (N) grows to infinity with N 2 . A more detailed analysis of the N-behavior of critical couplings will be given elsewhere [15].…”
Section: Discussionmentioning
confidence: 64%
“…It is also interesting to extend the PCC algorithm to the problem of the vector order parameter. We have already succeeded in applying the PCC algorithm to the classical XY model, 24) and have shown that the PCC algorithm is useful not only for the analysis of the second-order transition but also for that of the transition of the Kosterlitz-Thouless type.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The clock model, being a bridge between different models, is expected to have various critical behavior under different values of q. Extensive studies [8][9][10][11][12][13][14][15] on the clock model had shown that, for q 4, the phase transition is Ising-like, and for q ! 6, it is XY-like.…”
Section: Introductionmentioning
confidence: 99%